The Spectrum of Oesophagal Varices, Portal Hypertensive Gastropathy and Child Pugh’s Class in Cirrhotic Patients at Tertiary CareHospital - Farooq, Muhmmad Asif; Yasin, Muhammad Awais; Parveen, Bushra; Mansoor, Hala; Khattak, Abdul Latif; Siddique, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find the association of Child-Pugh’s Class with oesophagal varices and portal hypertensive gastropathy in cirrhotic patients at CMH Lahore. Study Design: Cross sectional study Place and Duration of Study: Department of Gastroenterology and Department of Pathology, Combined Military Hospital Lahore Pakistan, from Feb to May 2021. Methodology: All patients with cirrhosis of the liver, irrespective of aetiology, who underwent upper gastrointestinal endoscopy, were included in the study. Lab data was retrieved from the Pathology Department to calculate Child Pugh’s score. Endoscopic findings of oesophagal varices and portal gastropathy were recorded and their correlation/association with Child-Pugh’s Class was calculated separately by using Pearson’s coefficient. Results: A total of 148 patients were included in the study. Male patients were 90(60.8%) and female were 58(39.2%). The age range was 27-85 years, with the mean of patients being 55.93±13.19 years. Association of Child Pugh’s Class with oesophagal varices and portal hypertensive gastropathy revealed that higher grades of oesophagal varices (Grade-lll) and severe portal hypertensive gastropathy were found in Child Pugh’s Class-B (13.51%, 14.18%) and C (15.54%, 16.2%) as compared to Class- A (4.72 %, 1.35%). Child-Pugh’s Class positively correlates with both oesophagal varices and portal hypertensive gastropathy by Pearson’s coefficient r=0.594 and 0.035, respectively; both have significant p values (p <0.05). Conclusion: Child-Pugh’s Class has a positive correlation with both oesophagal varices and portal hypertensive gastropathy in patients with cirrhosis